Analisis kemampuan literasi numerasi mahasiswa pada implementasi program kampus mengajar - Yuwono, Muhammad Ridlo; Zudha Ferryka , Putri; Setyandari, Ana; Munif, Fika Aisyah (IKIP Siliwangi, 2024)
The aim of this research is obtain a profile of the numeracy literacy abilities of students who have participated in the Teaching Campus program through analysis of the problem solving. This type of research is a case study. The subjects of this research were alumni of the Class 3 Teaching Campus at Widya Dharma University. Research data collection uses test methods and interview methods. The research instruments are the main instrument (researcher) and auxiliary instrument (numeracy literacy test). This research uses triangulation techniques to obtain valid data. The results of this research are (1) in text type questions students mention important information, do not formulate the problem, do not write down strategies, solve the problem correctly, check again without alternative solutions; (2) on text and image type questions, students mention important information and formulate problems, convey strategies, implement strategies with wrong image patterns, recheck answers; and (3) on text and table type questions, students mention important information and formulate the problem briefly, do not convey strategies, solve problems by paying attention to tables, and are less careful in analyzing text and table.